The Impact of Short-Term Supplementation With Guanidinoacetic Acid and Creatine Versus Creatine Alone on Body Composition Indices in Healthy Men and Women: Creatine-Guanidinoacetic Acid Affects Body Composition - Sonja Baltic; David Nedeljkovic; Nikola Todorovic; Laszlo Ratgeber; Jozsef Betlehem; Pongrac Acs; Valdemar Stajer; Sergej M. Ostojic (Journal of Nutrition and Metabolism)
The main objective of this pilot study was to compare the effects of short-term supplementation with a mixture containing creatine and guanidinoacetic acid (GAA) versus creatine alone on body composition indices in men and women. Twenty-three apparently healthy young adults (mean age: 21.4 ± 0.6 years; 10 females) were randomly assigned to receive either a mixture (consisting of 2 g of creatine monohydrate and 2 g of GAA) or an equimolar amount of creatine monohydrate in a pretest–posttest control group experimental crossover design. After the intervention period, participants entered a 2-week washout phase to minimize any residual effects of the treatment. Body composition was assessed using a multifrequency bioelectrical impedance analysis at baseline (preadministration) and at the 7-day follow-up (postadministration). A significant interaction effect was found for extracellular mass (p=0.009), with creatine–GAA outperforming creatine in augmenting extracellular mass across the whole sample. In the male subsample, creatine was superior to the mixture in increasing intracellular water (p=0.049), whereas the mixture increased extracellular mass, contrasting with the reduction observed with creatine alone (p=0.008). No significant differences between interventions were reported in the female subsample (p>0.05), indicating that adding GAA to creatine may produce unique, sex-specific effects on body composition. Further studies are needed to validate our findings across different demographic cohorts and various interventional regimens.